2005
DOI: 10.1038/sj.bjp.0706062
|View full text |Cite
|
Sign up to set email alerts
|

Selective release of ATP from sympathetic nerves of rat vas deferens by the toxin TsTX‐I from Brazilian scorpion Tityus serrulatus

Abstract: 1 The effects of the main component of the Tityus serrulatus scorpion venom, toxin TsTX-I, were studied on the contractility and release of neurotransmitters in the rat vas deferens. Since TsTX-I is known to act on sodium channels, we used veratridine, another sodium channel agent, for comparison. 2 Toxin TsTX-I induced concentration-dependent contractions with an EC 50 value of 47.870.1 nM and a maximum effect of 84.4710.4% of that for BaCl 2 . 3 Contractions by TsTX-I were abolished by denervation or tetrodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
(80 reference statements)
0
16
0
Order By: Relevance
“…Isolated vas deferens preparations contract in a frequency-dependent manner, and the contractions are mediated by different ion channels and neurotransmitters including noradrenaline and ATP (7,32). At low frequencies, the response to electrical stimulation is mediated primarily by N-type Ca 2+ channels and ATP, and at higher frequencies, there are also other types of Ca 2+ channel and noradrenergic transmitter participation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated vas deferens preparations contract in a frequency-dependent manner, and the contractions are mediated by different ion channels and neurotransmitters including noradrenaline and ATP (7,32). At low frequencies, the response to electrical stimulation is mediated primarily by N-type Ca 2+ channels and ATP, and at higher frequencies, there are also other types of Ca 2+ channel and noradrenergic transmitter participation (29).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] One end of the vas deferens was fixed to the organ chamber, and the other end was attached by means of a silk surgical suture to a force-displacement transducer (model FT 302; CB FT-302, iWORX, NH, USA) connected through a bridge amplifier to a PowerLab recorder (ADInstruments, Castle Hill, NSW, Australia) coupled to a computer. Contractions were recorded and the data stored in Chart 4.2.1 software (ADInstruments, Warwick, USA).…”
Section: Functional Study Of Sympathetic System and Pharmacological Rmentioning
confidence: 99%
“…17,18 After an equilibration period of 30 min, the organ was subjected to electrical field stimulation of 60 V, 1 ms duration and frequencies of 2 and 5 Hz, by means of a Grass S88 stimulator (Grass USA). In neurogenic contractions induced by the electrical field stimulation, two steps can be distinguished, namely, phasic (purinergic, ATP dependent) and tonic (noradrenergic).…”
Section: Nerve-mediated Contractionmentioning
confidence: 99%
“…Several studies have demonstrated its peripheral action such as pre-junctional sensitization of the guinea pig vas deferens (Sampaio et al 1983;Arantes et al 1989), increase in acetylcholine output through the activation of Na + channels in the motor nerve terminals (Oliveira et al 1989), increase in the volume, acidity and pepsin output of rat stomach (Cunha-Melo et al 1991), prolongation of the hypotensive effect in anesthetized rats (Sampaio et al 1991), reduction in the contractile force of isolated rat atria (Couto et al 1992) and increase in pancreatic exocrine secretion Fletcher et al 1996). More recently, it was demonstrated that this toxin causes a concentration-and timedependent increase in the release of norepinephrine and epinephrine from bovine adrenal medullary chromaffin cells (Conceição et al 1998) and produces a selective release of purines from postganglionic sympathetic nerves in the rat vas deferens without modifying the overflow of noradrenaline (Conceição et al 2005). Nevertheless, the literature lacks studies about the effect of this toxin on the central nervous system.…”
Section: Introductionmentioning
confidence: 95%